Slowed muscle oxygen uptake kinetics with raised metabolism are not dependent on blood flow or recruitment dynamics. (27th February 2014) - Wüst, Rob C. I.; McDonald, James R.; Sun, Yi; Ferguson, Brian S.; Rogatzki, Matthew J.; Spires, Jessica; Kowalchuk, John M.; Gladden, L. Bruce; Rossiter, Harry B.
Abstract : Key points: A slow adjustment of skeletal muscle oxygen uptake ( V ̇ O 2 ) to produce energy during exercise predisposes to early fatigue. In human studies, V ̇ O 2 kinetics are slow when exercise is initiated from an elevated baseline; this is proposed to reflect slow blood flow regulation and/or recruitment of muscle fibres containing few mitochondria. To investigate this, we measured V ̇ O 2 kinetics in canine muscle, with experimental control over muscle activation and blood flow. We found that V ̇ O 2 kinetics remained slow when contractions were initiated from an elevated baseline despite experimentally increased blood flow and uniform fibre activation. These data challenge our current understanding of the control of muscle V ̇ O 2 and demand consideration of new alternative mediators for V ̇ O 2 control. Abstract: Oxygen uptake kinetics (τ V ̇ O 2 ) are slowed when exercise is initiated from a raised metabolic rate. Whether this reflects the recruitment of muscle fibres differing in oxidative capacity, or slowed blood flow ( Q ̇ ) kinetics is unclear. This study determined τ V ̇ O 2 in canine muscle in situ, with experimental control over muscle activation and Q ̇ during contractions initiated from rest and a raised metabolic rate. The gastrocnemius complex of nine anaesthetised, ventilated dogs was isolated and attached to a force transducer. Isometric tetanic contractions (50 Hz; 200 ms duration) via supramaximal sciatic nerve stimulation were used to manipulate metabolic rate: 3 min stimulation at 0.33 Hz (S1), followed by 3 min at 0.67 Hz (S2). Circulation was initially intact (SPON), and subsequently isolated for pump‐perfusion (PUMP) above the greatest value in SPON. Muscle V ̇ O 2 was determined contraction‐by‐contraction using an ultrasonic flowmeter and venous oximeter, and normalised to tension‐time integral (TTI). τ V ̇ O 2 /TTI and τ Q ̇ were less in S1SPON (mean ± s.d.: 13 ± 3 s and 12 ± 4 s, respectively) than in S2SPON (29 ± 19 s and 31 ± 13 s, respectively; P  < 0.05). τ V ̇ O 2 /TTI was unchanged by pump‐perfusion (S1PUMP, 12 ± 4 s; S2PUMP, 24 ± 6 s; P  < 0.001) despite increased O2 delivery; at S2 onset, venous O2 saturation was 21 ± 4% and 65 ± 5% in SPON and PUMP, respectively. V ̇ O 2 kinetics remained slowed when contractions were initiated from a raised metabolic rate despite uniform muscle stimulation and increased O2 delivery. The intracellular mechanism may relate to a falling energy state, approaching saturating ADP concentration, and/or slowed mitochondrial activation; but further study is required. These data add to the evidence that muscle V ̇ O 2 control is more complex than previously suggested.